Makna Kata Γλώσσῃ (Bahasa Lidah) Menurut 1 Korintus 14:2 - Binar, Sri; Lianto , Michael (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
The debate over whether "tongues" or "language" in the Bible, translated as "Bahasa Roh" in the Indonesian Bible version, still continues, especially among Pentecostal and Protestant communities. The ongoing discussion revolves around whether the baptism of the Holy Spirit continues to this day and whether the "Bahasa Roh" referred to in the Bible denotes meaningless utterances as practiced in modern Pentecostal churches. Pentecostals argue that speaking in tongues is the initial evidence and fundamental pattern of the baptism of the Holy Spirit, while others refute this claim. The primary basis for both arguments is 1 Corinthians 14:2. The purpose of this research is to uncover the true meaning of "Bahasa Roh" according to the Bible as written in 1 Corinthians 14:2. This research is qualitative research using the method of exegesis. The analyses used in this research are contextual analysis, grammatical analysis, and historical analysis. The results of the research reveal that γλώσσῃ (tongue) refers to utterances that cannot be understood and were never learned, as a result of the prompting of the Holy Spirit. As part of the gifts of the Spirit, it is necessary to serve one another well and glorify God, but it should not be the main focus because the most important aspect of all gifts is the driving motive, which is love.